Syrian norms of McNamara cephalometric analysis - AL SABBAGH, Rabab (International Arab Journal of Dentistry (IAJD), 2014)
McNamara’s cephalometric analysis is one of the most suitable analyses for diagnosis, treatment planning and treatment evaluation. Yet, no study has, till now, detected the norms of this analysis in a Syrian population. The current study aims to establish cephalometric norms of McNamara’s analysis for Syrians with normal occlusion and to compare these norms between males and females. The study was conducted using lateral cephalometric radiographs of a sample comprised of 100 adolescents with normal, permanent occlusion. The results showed that there were statistically significant gender differences among Syrians for 11 out of 15 cephalometric variables. The comparison revealed statistically significant differences in most variables between Syrian males and females. Therefore, It would be preferable to use the specific Syrian norms.